Studi Tentang Kekerasan Berbasis Gender Online - Nurdiana Sari (Jurnal Dewantara, 2021)
Prevention of KBGO in children can be done from an early age, one of which is by dialogical assistance in using gadgets in children. As parents, we must wisely sort and choose the right time and spectacle for our children. Next we are encouraged to educate what has been watched earlier. Some of the phenomena that occur today are children over the age of 8 who are addicted to games in which they have to consume advertisements that should be included in the category of adult advertisements, there are even some games that offer to login and use applications such as Tik-Tok, SnackVideo and others whose applications really need extra supervision from parents. Not only that, the presentation of games for children must also be wise and adapted to the age of our children, because not all games are appropriate and good for children, and even children should avoid it because it will affect the character.